2023
DOI: 10.1021/acsami.2c22571
|View full text |Cite
|
Sign up to set email alerts
|

Noncentrosymmetric Lanthanide-Based MOF Materials Exhibiting Strong SHG Activity and NIR Luminescence of Er3+: Application in Nonlinear Optical Thermometry

Abstract: Optically active luminescent materials based on lanthanide ions attract significant attention due to their unique spectroscopic properties, nonlinear optical activity, and the possibility of application as contactless sensors. Lanthanide metal-organic frameworks (Ln-MOFs) that exhibit strong second-harmonic generation (SHG) and are optically active in the NIR region are unexpectedly underrepresented. Moreover, such Ln-MOFs require ligands that are chiral and/or need multistep synthetic procedures. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…This is because polycrystalline, micro-and nanosized materials are composed of a large number of small crystallites with random orientations, which allows for the detection of averaged NLO signal such as SHG. [1,18,25,56] Hence, precise phase-matching for each crystal is no longer required. Therefore, we chose polycrystalline LiNbO 3 nanoparticles (NPs) as the phase for designing our NLO material platform (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because polycrystalline, micro-and nanosized materials are composed of a large number of small crystallites with random orientations, which allows for the detection of averaged NLO signal such as SHG. [1,18,25,56] Hence, precise phase-matching for each crystal is no longer required. Therefore, we chose polycrystalline LiNbO 3 nanoparticles (NPs) as the phase for designing our NLO material platform (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…To quantitatively evaluate the SHG performance of our NPs, we compare the signal intensity to that of KDP powders, commonly employed as reference (Figure 3d; Figure S11, Supporting Information). [14,17,18,60] The SHG signal from the LiNbO 3 NPs is significantly higher (up to 80-fold) compared to the reference KDP powders, and it is hardly influenced by the Ln doping (Figure S11, Supporting Information). A similar excitationwavelength dependence of the SHG intensities is observed for our LiNbO 3 NPs and KDP powders (Figure 3d; Figure S12, Supporting Information).…”
Section: Wavelength-dependent Shg and Thg Of The Nanoparticles As Pow...mentioning
confidence: 99%
See 2 more Smart Citations
“…To date, it is still a great challenge to develop suitable strategies to optimize the separation rate of carriers and maximize the photocatalytic activity of BiOBr. It has been demonstrated that the size and shape of photocatalysts have an impact on photocatalytic performance. For example, a 2D nanosheet structure with a large specific surface area provides more reaction sites and thus promotes photocatalytic reactions. Among the various shapes of BiOBr, the flower-shaped microsphere structure of BiOBr enriched with nanosheets maximizes its specific surface area while promoting the adsorption of pollutants . In addition, doping rare earth ions into BiOBr is an effective way to enhance the separation efficiency of electron–hole pairs. However, the rapid recombination of photogenerated carriers and the high surface energy of microspheres result in severe aggregation, thus imposing limitations on photocatalytic activity. Assembling microspheres on fibers provides a feasible way to prevent agglomeration and facilitates recycling. …”
Section: Introductionmentioning
confidence: 99%